The Effect of Classical Guidance Services Using the Snakes and Ladders Game on Increasing Self-Confidence in Grade 5 Students at UPT SDN 01 Limo Kaum: Pengaruh Layanan Bimbingan Klasik Menggunakan Permainan Ular Tangga terhadap Peningkatan Kepercayaan Diri Siswa Kelas 5 di UPT SDN 01 Limo Kaum - Fadhiah al Hafizd; Dasril; Silvianetri; Rafsel Tas’adi (MARAWA: Jurnal Masyarakat Religius dan Berwawasan, 2026)
This research is motivated by the presence of students who are less actively involved in learning activities, feel afraid or embarrassed when having to appear in front of the class, and show anxiety when interacting with peers and teachers1. This problem indicates low self-confidence that can hinder students' academic potential and personal development. This study aims to determine whether there is a significant influence of providing classical guidance services with the snakes and ladders game media on increasing the self-confidence of 5th grade students at UPT SDN 01 Limo Kaum. The research method used is quantitative with the type of experimental research. This study uses a One Group Pre-test Post-test design. This method is carried out by giving an initial test (pre-test) before treatment and a final test (post-test) after treatment in one experimental group. This aims to measure the extent of the influence of the actions given to students. The population in this study were 20 fifth-grade students at UPT SDN 01 Limo Kaum, with a research sample of 20 fifth-grade students selected using a random sampling technique. Data were collected through a self-confidence scale consisting of 40 statement items and analyzed using a t-test and SPSS data processing. The results showed a significant increase in self-confidence scores after the treatment. The average pre-test score of 13.04 increased to 16.86 in the post-test. Based on the hypothesis test, the calculated t value was greater than the t table, thus rejecting the null hypothesis H0 and accepting the alternative hypothesis Ha. Therefore, it can be concluded that classical tutoring services using the snakes